Eticizar a assistência na terapia intensiva: práticas e dificuldades da humanização experienciadas pelos médicos de um hospital público de Pernambuco. - Correia, Raissa Inojosa do Rego Barros (2020)
Scenario: Technological advances have contributed to the improvement of health care, with an emphasis on critical units, particularly in intensive care services. This sector for the care of critically ill or at-risk patients requires uninterrupted assistance, in addition to specialized equipment and human capital. However, it is a constant challenge for members of the intensive care unit team to humanize the provision of care. Objective: This research is the result of the need for a reflection on the humanization of care in intensive care from the subjective perspectives of the subjects under study in order to understand the experience lived by doctors, as well as the difficulties faced in this context in the intensive care unit of a public hospital in Pernambuco. Method: For this purpose, the method used was a qualitative research, which had as a research instrument the semi-structured reflective interviews conducted with doctors working in the intensive care unit of one of the largest public hospitals in Pernambuco. The comprehensive analysis of the phenomenon under investigation it was carried out through the Analysis of the Situated Phenomenon, structured by Martins and Bicudo. Results and Discussion: In the analysis of data from professionals, four thematic categories emerged: 1) Humanization in health: a concept under construction; 2) The dialectic expressed in the doctors' discourse on humanization and dehumanization; 3) Between theory and existing praxis: daily difficulties in the humanization process in the intensive care unit; and 4) The confrontation between medical training and humanization. With a better understanding of humanized practices in health care, the aim is to transform the knowledge obtained from research into social practice.